E-WOM, Kepercayaan Konsumen, dan Minat Konsumen dalam Membeli Produk Fashion di E-Commerce - Simamora, Virgo (Research and Community Service UNIVERSITAS KALBIS, 2023)
The growing number of online purchases each year shows how appealing the e-commerce sector is today. This study focuses on how consumer trust serves as a mediator between e-WOM and consumer interest. In this research, one hundred millennials are involved as respondents. The study samples consisted of women, millennials, living in DKI Jakarta who actively engaged in e-commerce. The results of this study found that consumer interest in engaging in e-commerce transactions is influenced by electronic word-of-mouth (E-WOM). Similarly, customer trust affects consumers' purchasing intentions to buy fashion products in e-commerce. Lastly, this study demonstrates the function of consumer trust as a mediating variable in the relationship between e-WOM and millennial enthusiasm for buying fashion products through e-commerce. Keywords : e-WOM, trust, purchasing intentions.